PENGEMBANGAN MEDIA PEMBELAJARAN ALAT PERMAINAN EDUKATIF (APE) KODING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK IRMA KOTA SERANG - Siti Nurhopipah; Zulfitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop appropriate and effective coding Educational Game Tools (APE) learning media to improve the cognitive abilities of children aged 5-6 years at IRMA Kindergarten in Serang City. This research uses the Research and Development (R&D) method by combining the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The product developed is in the form of APE coding media as an innovative, concrete, and fun learning tool for early childhood. The development of APE coding media has been proven to improve the cognitive abilities of children aged 5-6 years, especially in logical thinking, recognizing patterns, solving simple problems, and understanding instructions sequentially. The results of the study showed that APE coding media obtained a feasibility percentage of 100% from media experts with a very valid category, so it was considered appropriate in terms of physical presentation, images, illustrations, security, and suitability with early childhood characteristics. The results of the effectiveness test also showed an increase in children's cognitive abilities, which was marked by an increase in pre-test scores from 95 to 151 in the post-test with an N-gain value of 86.15% in the effective category. The implications of this study confirm that the use of educational game-based learning media can be an effective alternative in supporting active and meaningful learning in kindergarten. Therefore, APE coding media is recommended to be used continuously and further developed in broader learning aspects and contexts.